C. McGinn. Why Is It Good to Be Alive? / trans. from Engl. R. L. Kochnev - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
The essay raises the problem of the value of life. For living organisms like us, it appears to be an unconditionally good. It seems that the necessary grounds for such an attitude must be in the ontological structure of life itself. But an impartial analysis shows that the value of life is something external to life itself.